Global Comparatives Statics in General Equilibrium: Model Building from Theoretical Foundations - James R. Markusen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
International trade economists made seminal contributions to general equilibrium theory, moving away from an emphasis on existence of equilibrium to algebraic formulations which enabled us to characterize key relationships between parameters and variables, such as that between tariffs and domestic factor prices and welfare. But the analysis remained limited in value for policy evaluation: the analysis was local, it provided only qualitative results, it was limited to very small models, and strictly interior solutions had to be assumed. The contribution of this paper is pedagogic and methodological, providing a primer for those wishing to do or teach general equilibrium counterfactuals on (for example) structural models. I show how the tools from early local comparative statics analyses can be generalized via the use of Shepard's lemma, duality, complementarity and the Karush-Kuhn-Tucker theorem into a global, quantitative analysis of large changes in high-dimension models which also allows for regime changes and corner solutions. I then show how the resulting non-linear complementarity problem directly translates into a numerical model using GAMS (general algebraic modeling system).
Keywords: F50; D50; D58; 330; duality; complementarity; KKT conditions; global comparative statics; corner solutions; GAMS